2018
DOI: 10.1080/02701367.2018.1472365
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal Eccentrics Versus Traditional Loading in Improving Lower-Body 1RM: A Meta-Analysis

Abstract: The selection of SME over TRAD in RT programs designed to increase lower-body 1RM does not appear warranted in all populations. Further research should clarify the merit of periodic SME in TRAD-dominant RT programs as well as whether a differential effect exists in trained individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Neural adaptations might have been predominant because improvements at higher movement speed exceeded those at lower velocity (Figure 3). 10,11,16,29 The present findings support the assumption that eccentric‐only training elicits long‐lasting strength gains 14,15 . If high intensities are implemented, the repeated bout effect lasts between several weeks up to 6 months 15,16 This knowledge is important for coaches and scientists to optimally design and periodize sprint‐related strength training programs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Neural adaptations might have been predominant because improvements at higher movement speed exceeded those at lower velocity (Figure 3). 10,11,16,29 The present findings support the assumption that eccentric‐only training elicits long‐lasting strength gains 14,15 . If high intensities are implemented, the repeated bout effect lasts between several weeks up to 6 months 15,16 This knowledge is important for coaches and scientists to optimally design and periodize sprint‐related strength training programs.…”
Section: Discussionsupporting
confidence: 79%
“…Further effort is required to overcome the practical challenges (eg, ensuring a high execution quality) and impaired functionality (eg, unilateral NHEs with flexed hip across a reduced ROM) of NHE training. An optimal dose‐response relationship has to be established for this supramaximal exercise because it poses an extraordinarily high load on the athletes' hamstrings 29 . In this context, the guidelines of traditional resistance training (eg, 3‐4 sets with 8‐12 repetitions) are not adequate and will lead to poor execution quality, impaired adaptations and low compliance 19 …”
Section: Perspectivementioning
confidence: 99%
“…There were 407 records removed on title/abstract screening, 2 records could not be retrieved, and 23 records were excluded on full-text screening. Fourty-four 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 reviews (5 systematic reviews, 2 meta-regressions, 35 meta-analyses, 1 network meta-analysis, and 1 umbrella review) met the eligibility criteria and were included ( Fig. 1 ).The AMSTAR scores and QoE for the included systematic reviews range from 2 to 10 and 1 to 4, respectively ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a moderate-quality meta-analysis (QoE: Level 3) 46 found no differences between eccentric- or concentric-RT for improvement in peak torque (weighted mean difference: 3.71 N·m; 95%CI: –0.27 to 7.70; p = 0.07; n = 333) or 1RM (weighted mean difference: 1.07 kg; 95%CI: –0.22 to 2.37; p = 0.10; n = 72). Two moderate-quality reviews (QoE: Level 3) 17 , 38 provided insufficient evidence to determine an effect due to the low number of studies synthesized for the analysis (<5 studies) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these findings, other investigations [41,44] have found that high-velocity EO training (180 • •s −1 ) had a greater degree of transfer than slow velocity EO training (30 • •s −1 ) during isokinetic testing. Furthermore, one review [45] challenged whether EO provided any additional benefit over traditional training, suggesting that specific populations such as athletes and the untrained may respond differently to EO as a training stimulus depending on baseline strength capabilities.…”
Section: Strengthmentioning
confidence: 99%